2014
DOI: 10.1103/physrevb.89.020504
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting proximity effect in silicene: Spin-valley-polarized Andreev reflection, nonlocal transport, and supercurrent

Abstract: We theoretically study the superconducting proximity effect in silicene, which features massive Dirac fermions with a tunable mass (band gap), and compute the conductance across a normal|superconductor (N|S) silicene junction, the non-local conductance of an N|S|N junction, and the supercurrent flowing in an S|N|S junction. It is demonstrated that the transport processes consisting of local and non-local Andreev reflection may be efficiently controlled via an external electric field owing to the buckled struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 25 publications
0
88
0
Order By: Relevance
“…32. The bulk-boundary correspondence has not been taken into account within our scattering matrix formalism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32. The bulk-boundary correspondence has not been taken into account within our scattering matrix formalism.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently superconducting proximity effect in silicene has been investigated in Ref. 32 in which the authors have theoretically studied the behavior of electrical conductance in a normal-superconductor (NS) junction of silicene. Up to now, no experiment has been carried out in the context of proximity effect in silicene.…”
Section: Introductionmentioning
confidence: 99%
“…Here, motivated by experimental and some theoretical studies [16][17][18][19][20][21][22], we investigate the Josephson effect through the ML-MoS 2 both at its normal and spin-polarized (magnetic) states. If we induce conventional s-wave superconductivity in ML-MoS 2 via proximity, the Cooper pairs are formed from excitations from different (opposite) valleys and having opposite spins, very similar to the case of graphene [23].…”
mentioning
confidence: 99%
“…3 in terms of the exchange field of the right F region, h R , for three different lengths of the S region, where the pure CAR process (for h R = −h L < 0) is fully changed in the pure CT process (for h R = h L > 0) by changing the configuration of the magnetization directions from AP to P. The length dependence of the CT and CAR conductances will be explained in details in the following paragraphs. We note that the existence of a fully valley-and spin-polarized nonlocal charge current via the pure CAR (CT) process, without fixing of any parame- ter and for a wide range of the chemical potential of the F region, is the advantage of the proposed MoS 2 -based superconducting spin valve structure over the grapheneand silicene-based structures [13][14][15][16][17][18]. Therefore, we find that for all incoming electrons with µ 2 < µ F − eV ≤ µ 1 , the AR process is suppressed and the cross-conductance in the right F region depends crucially on the configuration of magnetizations in the two F regions.…”
Section: A Charge Conductancementioning
confidence: 99%
“…Unfortunately, in ordinary nonrelativistic systems, the small value of the CAR conductance is completely canceled by the conductance of another nonlocal process known as elastic electron cotunneling (CT) which does not involve Copper * leyla.majidi@ipm.ir pairs and is therefore a parasitic process [7]. Recently, it has been demonstrated that the atomically thin twodimensional (2D) crystals such as graphene and silicene are possible areas for CAR processes [13][14][15][16][17][18] where the magnitude of the CAR conductance can be enhanced in normal/superconducting/normal (N/S/N) and ferromagnetic/superconducting/ferromagnetic (F/S/F) hybrid structures. Cayssol [13] has predicted a pure CAR process without any valley-or spin-polarization in graphene-based N/S/N structure at the bias voltage eV = µ (µ is the chemical potential).…”
Section: Introductionmentioning
confidence: 99%